2014
DOI: 10.4103/0019-5545.140636
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of oral mucosal lesions among psychiatric inmates residing in central jail, Bhopal, Madhya Pradesh, India: A cross-sectional survey

Abstract: Aim:The aim of the current cross-sectional study was to assess oral mucosal lesions among psychiatric jail patients residing in central jail, Bhopal, Madhya Pradesh, India.Materials and Methods:The study subjects consisted of prediagnosed psychiatric patients residing in central jail, Bhopal. A matched control consisting of cross section of the population, that is, jail inmates residing in the same central jail locality was also examined to compare the psychiatric subjects. The WHO oral health assessment profo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It was found that most of the inmates with psychiatric issues had a habit of tobacco consumption. Furthermore, the study discovered a significant correlation between oral mucosal lesions with tobacco-related habits 18 . A local study conducted by Qadir et al revealed that out of the 433 inmates in Karachi, 89% were addicted to at least one addiction such as smoking, naswar, pan, gutka and manpuri, heroin, ganja (cannabis), charas (hashish form of cannabis), and opium 19 .…”
Section: Discussionmentioning
confidence: 92%
“…It was found that most of the inmates with psychiatric issues had a habit of tobacco consumption. Furthermore, the study discovered a significant correlation between oral mucosal lesions with tobacco-related habits 18 . A local study conducted by Qadir et al revealed that out of the 433 inmates in Karachi, 89% were addicted to at least one addiction such as smoking, naswar, pan, gutka and manpuri, heroin, ganja (cannabis), charas (hashish form of cannabis), and opium 19 .…”
Section: Discussionmentioning
confidence: 92%
“…in psychiatric inmates, 8.4% by Mehrotra et al ., 8.4% by Patel and Patel, 46.1% by Thada and Pai, and 64% by Patil etal. [ 1 2 3 5 17 20 21 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Oral lesions can be secondary to nutritional deficiency, trauma, infection, local irritation, ill-fitting denture, sharp tooth, electro galvanism, adverse oral habits, and systemic infections. [ 2 3 4 5 ]…”
Section: Introductionmentioning
confidence: 99%